Rape Survivors’ Sorrow: Major Depressive Symptoms and Sexually Transmitted Infection Among Adolescent Girls, Southwest Ethiopia - Belay EA; Deressa BG (Dove Medical Press, 2021)
Eyob Asefa Belay,1 Beshea Gelana Deressa2 1Department of Obstetrics and Gynecology, Jimma University, Jimma, Ethiopia; 2Department of Health Policy and Management, Jimma University, Jimma, EthiopiaCorrespondence: Beshea Gelana DeressaDepartment of Health Policy and Management, Jimma University, PO BOX: 378, Jimma, EthiopiaTel +251921833996Email tuniriyabesha@gmail.comPurpose: Rape is one of the sexual violence acts against women globally. Adolescent girls are vulnerable to this event and experience more severe and long-standing adverse effects. Thus, this study aimed to examine major depressive symptoms and associated factors and the level of sexually transmitted infection among female adolescents evaluated for rape cases at Jimma Medical Center.Patients and Methods: Institutional-based cross-sectional study was conducted among adolescent girls assessed for rape cases in Jimma Medical Center. Data were collected using structured questionnaire and entered into Epi Data version 3.1 then exported to SPSS version 21.0 for analysis. Descriptive statistics and regression analyses were carried out.Results: A total of 174 raped adolescent females took part in the study. Of the total participants, 155 (89.1%) of these individuals had major depressive symptoms (95 CI %, 84.5- 93.7%), while 85 (48.9%) of them had an STI (95% CI, 41.1- 56.9%). From logistic regression, place of residence (AOR 14.65, 95%, (p=0.002)), attending school currently (AOR 9.01, 95%, p=0.004), raped by hitting (AOR 17.67, 95%, p< 0.001) and unwanted pregnancy (AOR 14.68, 95%, p=0.001) were the variables associated with major depression.Conclusion: This study indicates that adolescents were suffering from several encumbrances like major depressive symptoms, sexually transmitted diseases and unwanted pregnancy. It also indicated that place of residence, school attending, and unwanted pregnancy had an association with major depressive symptoms. Therefore, the need for a comprehensive approach while treating this vulnerable group is highly recommended.Keywords: sexual assault, rape victims, sexual violence, Jimma, rape survivors